DIABETIC KETOACIDOSIS IN PREGNANCY - Novaković, Ivana; Todorović, Jovana; Dugalić, Stefan; Macura, Maja; Milinčić, Miloš; Gojnić, Miroslava (Sanamed, 2024)
Diabetic ketoacidosis (DKA) is one of the most serious and life-threatening complications of diabetes mellitus (DM), especially when it occurs during pregnancy, with a prevalence ranging from 0.5% to 3%. Pregnancy is considered a susceptible environment for the development of this type of metabolic imbalance due to its inherent physiological changes. Unspecific symptoms (vomiting, diarrhea, abdominal pain, etc.), especially in pregnant women, and the fact that ketoacidosis can develop even with normal glucose values (defined as euglycemic ketoacidosis), often lead to a delayed diagnosis. Evidence suggests that timely diagnosis and appropriate management of ketoacidosis are crucial in preventing adverse outcomes for both the mother and the fetus. Fetal outcomes are often dichotomous, resulting in either fetal demise (miscarriage/stillbirth) with a prevalence of 10% to 35%, or the birth of a healthy baby, with possible complications primarily related to diabetes mellitus itself. Additionally, case reports of ketoacidosis developing even in non-diabetic women due to other diseases (such as acute pancreatitis, appendicitis), as well as in those with gestational diabetes mellitus (GDM), further emphasize the importance of considering this condition in everyday clinical practice. The aim of this paper is to further elucidate the causes and course of this complication, as well as the outcomes for both mother and fetus, to contribute to a better overall understanding.
Keywords: diabetes mellitus; diabetic ketoacidosis; pregnancy